(untitled) (Journal of Educational Sciences, 2018)
The article gives an opportunity for students to practice theoretical knowledge obtained by integrating biotechnological research into methods of teaching biology in higher education institutions. With the help of biotechnological research, methods for conducting standard laboratory studies of pedagogical biology in higher educational institutions are proposed. Laboratory classes are conducted efficiently, using comprehensive technological methods, depending on the pedagogical skills of the teacher. Based on the use of biotechnological research, biologically active substances from high-water plants were determined. The subject of the study were aquatic plants Eichhornia crassipes, Pistia stratiotes, grown in a special liquid medium, under the conditions of luministate. The amounts of biologically active substances from aboveground and underground parts of aquatic plants were analyzed. Most of the biologically active ISSN 2520-2634 Journal of Educational Sciences. №2 (55). 2018 67 Ерназарова Г.И. және т.б. substances are alkaloids, amino acids, anthraquinones, proteins, carbohydrates, coumarins, polysaccharides, steroids, terpenes, phenolic acids and flavonoids. Methodical work is important in determining the method of detecting biologically active substances in special experimental work and analyzing the results obtained by developing research abilities of students. Key words: Eichhornia crassipes, Pistia stratiotes aquatic plants, biologically active substances.